Reactualizing living values education in the settlement of border land disputes - Fransiskus Markus Pereto Keraf; Yanuarius Sani Feka; Marsianus Falo; Yohanes Pebrian Vinney Mambur; Simon Juan Kune (Himpunan Pengembang Kurikulum Indonesia, 2025)
Resolving disputes between regions at the border, in general, must always involve interaction between the two countries. The resolution of the dispute must be through applicable international legal mechanisms and based on the results of international court decisions. Apart from using legal mechanisms, other methods that countries in dispute can take are diplomacy and mediation. This research examines the re-actualization of life values education used in resolving border disputes through mediation. The research approach used in this research is qualitative research with a case study model. Data collection uses observation techniques, interviews, and documentation studies. The data analysis technique uses the Miles and Huberman model, which consists of data reduction, data display, and conclusion. There is a model of stimulus values, receiving information, exploring real-world values, discussion and sharing information, personal emotions, and interpersonal communication, developed using the Living Values Education approach. The value model in implementing living values education can be internalized to resolve border disputes in the pre-mediation, implementation, and post-mediation stages. Abstrak Proses penyelesaian sengketa antar wilayah di perbatasan pada umumnya harus selalu melibatkan interaksi antar kedua Negara. Penyelesaian sengketa tersebut harus melalui mekanisme hukum internasional yang berlaku serta berdasarkan hasil penetapan pengadilan internasional. Selain menggunakan mekanisme hukum, adapun cara lain yang bias ditempuh oleh negara yang bersengketa yakni diplomasi dan mediasi. Penelitian ini mengkaji tentang reaktualisasi pendidikan nilai kehidupan yang digunakan dalam penyelesaian sengketa perbatasan melalui mediasi. Pendekatan penelitian yang digunakan dalam penelitian ini yakni penelitian kualitatif dengan model studi kasus. Pengumpulan data menggunakan teknik observasi, wawancara, dan studi dokumentasi. Adapun teknik analis data menggunakan model Miles and Huberman yang terdiri dari reduksi data, display data dan penarikan kesimpulan. Terdapat model nilai stimulus, menerima informasi, menjelajahi nilai – nilai dunia nyata, diskusi dan sharing informasi, emosional pribadi dan komunikasi interpersonal, dikembangkan menggunakan pendekatan Living Values Education. Model nilai dalam pengimplementasian living values education dapat diinternalisasi dalam penyelesaian sengketa perbatasan yang terdapat dalam tahapan pra mediasi, pelaksanaan, dan pasca mediasi. Kata Kunci: living values education; perbatasan; reaktualisasi